Influence of hand dominance, gender, and body mass index on hand grip strength - Mercy A. Agtuahene; Jonathan Quartey; Samuel Kwakye (AOSIS, 2023)
Background: Hand grip strength (HGS) measurements serve as an objective measure of upper extremity function. Reliable hand strength evaluation is vital for assessing treatment effectiveness. Objectives: To determine the influence of hand dominance, gender, and body mass index (BMI) on HGS among university students in Ghana. Method: In our cross-sectional study of 304 participants, height, weight, and BMI were measured using a stadiometer and weighing scale. Hand grip strength was assessed with a dynamometer. We compared HGS in dominant and non-dominant hands for males and females using a paired t-test and analysed the correlation between grip strength and weight, height, and BMI using Pearson's correlation coefficient. Results: The mean HGS for right-hand dominant (RHD) male participants was 35.62 kg (± 7.36) for the right hand compared with 32.84 kg (± 7.36) for the left hand. For females RHD the mean HGS in the right hand was 24.60 kg (± 6.42) compared to 22.12 kg (± 5.37) in the left hand. The mean weight, height and BMI of participants were 62.86 kg (± 10.30), 1.67 m (± 0.09) and 22.9 kg/m2 (± 4.9), respectively. A significant relationship existed between HGS and height (r = 0.492; p  0.01) as well as HGS and BMI (r = 0.290; p  0.01). However, no notable connection was found between HGS and weight (r = 0.001; p = 0.982). Conclusion: Hand grip strength was significantly stronger in the dominant hand of both males and females. Clinical implications: Physiotherapists should test HGS objectively and quantitatively for use in disease evaluation, diagnosis, and therapy.